How to leverage implementation research for equity in global health - Olakunle Alonge (BMC, 2024)
Abstract Implementation research (IR) is important for addressing equity in global health. However, there is limited knowledge on how to operationalize IR for health equity, and pathways for improving health equity through IR in global health settings. This paper provides an overview of guidance and frameworks for thinking about health equity as part of IR while noting the gaps in how this guidance and frameworks apply to global health. It proposes an approach to guide implementation teams in the application of IR for achieving equity in global health considering these gaps. It describes key equity considerations for different aspects of IR (i.e., implementation contexts, strategies, outcomes, and research designs). These considerations can be applied prospectively and retrospectively, and at different stages of IR. The paper further describes causal pathways, intervention levers, and strategies for achieving health equity in global health settings through IR. Central to these pathways is the power asymmetries among different actors involved in IR in global health and how these contribute to health inequities. The paper suggests recommendations and strategies for shifting the balance of power among these actors while addressing the structural and systemic determinants of health inequities as part of IR. Explicit considerations for health equity as part of implementation research and practice are needed for the achievement of global health goals. Such explicit considerations should look back as much as possible, and entail defining and analyzing health inequities and intervening on the underlying causes and mechanisms of health inequities as part of IR on a routine basis.